2005
DOI: 10.3358/shokueishi.46.33
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Acrylamide in a Processed Food Model System, and Examination of Inhibitory Conditions

Abstract: Acrylamide (AAm) is formed from asparagine (Asn) and reducing sugar during cooking of foods at high temperature. We examined the formation of AAm in a model system using a glass fiber filter paper, and looked for suitable conditions for inhibiting AAm formation. In frying, the formation rate was about 10 times that in a moistureless oven. Increase of frying temperature and frying time increased AAm formation when the residual moisture was 5῎ or less. AAm increased with increasing amount of glucose (Glc) additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The variation in the actual frying temperature contributed most to the variation in AA concentrations, followed by the variation in actual frying time while no obvious effect of reducing sugars was found [ 91 ]. Similarly, for soft breads the AA concentration varies from 0 to 203 μg/kg before toasting [ 5 ], and in biscuits, crackers and crispbreads the AA concentration varies from 0 to 1600 μg/kg, again depending on composition, types of crops, storage and cooking methods [ 12 , 13 , 14 ], which adds imprecision to the use of DQs and DRs in assessing dietary AA intake, as detailed information on origin, brands and cooking methods are seldom available. Furthermore, the use of probabilistic methods, in which the concentration range within the same food items is utilized by modeling the intake based on the distribution of AA levels [ 92 ], can improve the validity of the dietary assessment methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in the actual frying temperature contributed most to the variation in AA concentrations, followed by the variation in actual frying time while no obvious effect of reducing sugars was found [ 91 ]. Similarly, for soft breads the AA concentration varies from 0 to 203 μg/kg before toasting [ 5 ], and in biscuits, crackers and crispbreads the AA concentration varies from 0 to 1600 μg/kg, again depending on composition, types of crops, storage and cooking methods [ 12 , 13 , 14 ], which adds imprecision to the use of DQs and DRs in assessing dietary AA intake, as detailed information on origin, brands and cooking methods are seldom available. Furthermore, the use of probabilistic methods, in which the concentration range within the same food items is utilized by modeling the intake based on the distribution of AA levels [ 92 ], can improve the validity of the dietary assessment methods.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of AA depends mostly on the sugars, asparagine and other amino acids contents of the foods and the cooking temperature and duration, but it is also affected by storage methods, pH, and moisture content, as well as cooking methods [ 12 , 13 , 14 ] ( Figure 1 ). The concentration of AA can, therefore, vary even within the same kinds of food items for instance in potato crisps where concentrations range from 0 to almost 2000 μg/kg [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Other researchers have reported methods of analyzing the AAm contained in certain foods 3,4) and AAm levels in various processed foods have been studied. 5,6) It was found that heating the asparagines (Asn) and reducing sugars in food contributes to the formation of AAm, [7][8][9] but details about the mechanism for AAm formation and how such formation can be inhibited have yet to be fully understood. The purpose of our study was to clarify this mechanism of AAm formation and its inhibition using a fried model system based on sliced pieces of potato.…”
mentioning
confidence: 99%
“…Therefore, many studies have investigated the mechanism of acrylamide formation, as well as various methods for suppressing acrylamide formation (Becalski et al, 2004;Ishihara et al, 2005;Pedreschi et al, 2004;Palazoğlu et al, 2010;Zyzak et al, 2003). Generally, the formation of some acrylamide is unavoidable during food processing.…”
Section: Discussionmentioning
confidence: 99%